Evaluating Muscle Fatigue With Non-Invasive Approaches: A Review of Methods, Metrics, and Implications - Roberto F. Pitzalis; Beatrice Lagomarsino; Indya Ceroni; Nicholas Cartocci; Jamil Ahmad; Giulia A. Albanese; Jacopo Zenzeri; Christian Di Natali; Luigi Monica; Darwin G. Caldwell; Maura Casadio; Jesus Ortiz (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
An accurate and reliable assessment of muscle fatigue is crucial for understanding its underlying mechanisms, monitoring training adaptations, evaluating rehabilitation progress, and optimizing performance in sports and occupational settings. Over the years, numerous methods and metrics have been developed to quantify and characterize muscle fatigue. This paper comprehensively reviews the various assessment techniques used to measure muscle fatigue, encompassing physiological and functional perspectives based on questionnaires, biosignals, and robotics interfaces. By critically evaluating the strengths, limitations, and applications of these assessment methods, this article aims to provide researchers, clinicians, and practitioners with valuable information for selecting appropriate tools and interpreting the results in the context of research on muscle fatigue. In addition, it highlights emerging technologies and innovative approaches that hold promise in advancing our understanding of muscle fatigue and its implications for human performance.